TEACHING READING COMPREHENSION BY USING HERRINGBONE TECHNIQUE TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 11 LUBUKLINGGAU - ardayati ardayati; Herlina Herlina (STKIP PGRI Lubuklinggau, 2020)
The problem of this research was “Is it significantly effective to teach Reading Comprehension by using herringbone technique to the eighth grade students of SMPN 11 Lubuklinggau”? The objective was to find out whether or not it is effective to improve reading comprehension by using herringbone technique. The research method was pre experimental. The population of this research was 173 eighth grade students. The sample was taken through cluster random sampling. The result was 30 students of VIII.5 class students. The data were analyzed through four techniques: 1) Students’ Individual Score, 2) Minimum Mastery Criteria, 3) Normality and 4) Paired t-test calculation. The result of this study: (1) The mean students’ score in the pre-test was 61.33, (2) The mean score of post-test was 70.33 and (3) the result of paired t-test was 8.18, which was higher than 1.699 value of the t-table of 29 (30-1) with 0.05 significant level for one tailed-test. Based on the result of the paired t-test calculation showed that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It was effective to teach reading comprehension by using herringbone technique to the eighth grade students of SMPN 11 Lubuklinggau .